'A Table, A Cup, A Meowing Cat': Marie Howe's Theopoetics of the Ordinary. (18th September 2019) - Cunning, Andrew
Abstract: This article connects the work of contemporary poet, Marie Howe (1950–) to a lineage of American writing dedicated to and founded on 'the ordinary'. Beginning with Emerson and the transcendentalists, the argument is made that a largely Protestant tradition of American poetry and theology runs from Emerson and Whitman, through Elizabeth Bishop and Wallace Stevens, to Marilynne Robinson. Having established a distinctly American and specifically Protestant tradition of writing sourced from the mundane and the particular, it is shown how Marie Howe's poetry is in dialogue with this lineage, particularly in her overtly theological third collection, The Kingdom of Ordinary Time (2008). The article concludes with a close reading of Howe's poem 'The Teacher' from Magdalene (2017) and demonstrates how Howe ultimately disrupts the Emersonian tradition through her metaphor-less poetry. Using the Lord's Supper as a motif, it is shown how Howe's poetry opts for a Catholic approach to symbol, metaphor and transcendence, diverging theologically from Emerson, Stevens and Robinson's expectations of 'the ordinary'.